Current Practice of Therapeutic Hypothermia for Mild Hypoxic Ischemic Encephalopathy. (June 2019) - Saw, Chia L.; Rakshasbhuvankar, Abhijeet; Rao, Shripada; Bulsara, M; Patole, Sanjay
Context: Therapeutic hypothermia is the recommended treatment for neonates with moderate or severe hypoxic ischemic encephalopathy (HIE). There is an increasing trend to use therapeutic hypothermia even in infants with mild hypoxic ischemic encephalopathy, even though there is little evidence to support/refute this. Objective: To estimate the incidences of mild hypoxic ischemic encephalopathy among infants who received therapeutic hypothermia, and its short- and long-term outcomes. Data Sources and Study Selection: PubMed, Embase, CINAHL, and Cochrane library were searched to identify observational studies reporting on therapeutic hypothermia in term and near-term infants with mild hypoxic ischemic encephalopathy. The JBI (Joanna Briggs Institute) tools were used to assess the risk of bias in the included studies. Random effects meta-analysis was conducted to find out the percentage of cooled infants who had only mild hypoxic ischemic encephalopathy. Results: A total of 3590 citations were screened, of which 13 were included. Of the 2783 infants who received therapeutic hypothermia, 573 had mild hypoxic ischemic encephalopathy. Meta-analysis found that 22% of the infants who underwent therapeutic hypothermia had only mild hypoxic ischemic encephalopathy (95% confidence interval: 16%-27%; I 2 statistic = 90.5%). Five studies provided information on adverse effects of therapeutic hypothermia in mild hypoxic ischemic encephalopathy. The reported adverse effects were extreme hypothermia, bradycardia, hypoglycemia, sepsis, skin necrosis, pulmonary hypertension, and systemic hypotension.Limitation: The limitations included relatively small sample size and the lack of data for short- and long-term neurodevelopmental outcome. Conclusions: A significant proportion of infants who received therapeutic hypothermia had mild hypoxic ischemic encephalopathy. Randomized trials are urgently needed to evaluate the efficacy and safety of therapeutic hypothermia in infants with mild hypoxic ischemic encephalopathy.